2010
DOI: 10.3354/dao02144
|View full text |Cite
|
Sign up to set email alerts
|

Helminths and lipid peroxidation in Astyanax aeneus (Pisces: Characidae) from a river in the humid subtropics of southeastern Mexico

Abstract: Xenobiotic mixtures in aquatic ecosystems may compromise fish health by inducing oxidative stress, decreasing resistance, and fostering susceptibility to pathogens such as helminths. Lipid peroxidation (LPO) is one of the most commonly used methods to evaluate oxidative stress. The present study examines the potential correlations between LPO in liver, muscle, and gill and the presence of helminths in Astyanax aeneus from a subtropical river in Mexico. Five helminth species were identified: the trematodes Uvul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Some studies focused on the spatial variation of parasites of riverine fish have shown that the composition of parasite communities is relatively persistent (Knipes and Janovy, 2009; Ferrari-Hoeinghaus et al, 2006; Ferreira-Sobrinho and Tavares-Dias, 2016). By contrast, other studies report considerable changes in the community structure across such a spatial gradient (Weichman and Janovy, 2000; Bellay et al, 2012; Acosta et al, 2015; Córdova and Pariselle, 2007; Espinal-Carrión and López-López, 2010). Hence, doubts remain as to what extent fish parasite communities in a river are independent between host populations that inhabit that river.…”
Section: Introductionmentioning
confidence: 72%
“…Some studies focused on the spatial variation of parasites of riverine fish have shown that the composition of parasite communities is relatively persistent (Knipes and Janovy, 2009; Ferrari-Hoeinghaus et al, 2006; Ferreira-Sobrinho and Tavares-Dias, 2016). By contrast, other studies report considerable changes in the community structure across such a spatial gradient (Weichman and Janovy, 2000; Bellay et al, 2012; Acosta et al, 2015; Córdova and Pariselle, 2007; Espinal-Carrión and López-López, 2010). Hence, doubts remain as to what extent fish parasite communities in a river are independent between host populations that inhabit that river.…”
Section: Introductionmentioning
confidence: 72%